FAKTOR YANG BERPENGARUH TERHADAP KEJADIAN ASFIKSIA NEONATORUM DI RSUD BATARA GURU BELOPA - Devianti Tandiallo devianti; Fitriana Ibrahim; Jumriana Ibriani; Astuti Suardi; Ulvy Pratiwi; Hadija; Sry Wahyuni (Bina Generasi : Jurnal Kesehatan, 2023)
Asphyxia is an emergency event in the form of spontaneous breathing failure immediately after birth. It is very risky for death when the fetus does not breathe spontaneously and regularly so that it can reduce oxygen and increase carbon dioxide, which has bad consequences for continuing life. The cause of early neonatal death at Batara Guru Belopa Hospital is Asphyxia. Factors related to the incidence of asphyxia neonatorum at Batara Guru Belopa Hospital in 2021 This study uses a descriptive correlational method with a cross-sectional time approach. Sampling using the Slovin formula amounted to 62 respondents. Data collection tools using medical records Bivariate data analysis using the Chi-Square test shows that the incidence of asphyxia neonatorum is 52 infants, and infants who do not experience asphyxia neonatorum are 10 infants. There is a relationship between maternal age and neonatal asphyxia (p = 0.008), there is a relationship between parity and neonatal asphyxia (p = 0.000), there is a relationship between low birth weight (LBW) and neonatal asphyxia (p = 0.013), and there is a relationship between premature rupture (PROM) of membranes and neonatal asphyxia (p = 0.021). For institutions, it is hoped that the results of this study can be useful input for students, especially in preventing Neonatal Asphyxia so that it does not cause antenatal and neonatal deaths. Keywords: Asphyxia, maternal age, parity, LBW, PROM